Faktor Penyebab Rendahnya Minat Belajar Siswa dalam Pembelajaran Matematika Kelas VI Sekolah Dasar Nageri 12 Baruh-Bukit - Friska Mega Putri; Safrizal (Jurnal Riset Madrasah Ibtidaiyah, 2023)
The low interest of students in learning mathematics is a finding/problem that must be done. This study aims to find out what are the factors causing low student interest in learning mathematics in grade VI at SD Negeri 12 Baruh Bukit. This research activity was carried out by means of interviews, observation, and documentation. This research was conducted using qualitative methods with the type of research analysis case study (case study), the subjects in this study were class teachers, students VI, and parents of students. The key instrument of this research is the researcher herself, but in practice, the researcher uses tools such as cameras, tape recorders, interview guides, and observation guidelines. The technique used is snowball sampling. Based on the research that has been done, it was found that several factors influence students' interest in learning mathematics, that the factors causing low student interest in learning mathematics are as follows: internal student factors can be shown by 1) student attitudes 2) students' assumptions/considering that learning mathematics is scary, difficult learning. Students do not keep up with developments other than that there are many formulas in learning mathematics and as a result, students' math scores vary (low). Factors causing the lack of interest in student learning also come from external factors, namely environmental factors of students, lack of learning facilities, and lack of attention from parents (family).